1992
DOI: 10.1002/hep.1840160618
|View full text |Cite
|
Sign up to set email alerts
|

Preformed Lymphocytotoxic Antibodies: the Effects of Class, Titer and Specificity on Liver Vs. Heart Allografts

Abstract: The effect on liver and heart allograft survival (ACI rats to Lewis rats) was studied after three methods of recipient presensitization and after different intervals between sensitization and transplantation. With comparable lymphocytotoxic antibody titers, liver allografts always survived longer than heart grafts. The titer, class and specificity of the antibodies varied with the method of sensitization. Four skin grafts produced IgG and IgM lymphocytotoxic antibody titers of 1 : 2,000 to 4,000. The IgG fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The relative resistance of the transplanted liver to antigraft antibodies that cause hyperacute allograft and xenograft rejection (Kamada et al 1981, Starzl et al 1974, Houssin et al 1985, Furuya et al 1992, as well as the ability of the liver to shield other organs from humoral rejection (Fung et al 1988, Flye et al 1990) is of special interest for xenotransplantation (Valdivia et al 1993c). The shielding from humoral rejections is MHC-restricted for allografts (Fung et al 1988, Flye et al 1990).…”
Section: Humoral Immunitymentioning
confidence: 99%
“…The relative resistance of the transplanted liver to antigraft antibodies that cause hyperacute allograft and xenograft rejection (Kamada et al 1981, Starzl et al 1974, Houssin et al 1985, Furuya et al 1992, as well as the ability of the liver to shield other organs from humoral rejection (Fung et al 1988, Flye et al 1990) is of special interest for xenotransplantation (Valdivia et al 1993c). The shielding from humoral rejections is MHC-restricted for allografts (Fung et al 1988, Flye et al 1990).…”
Section: Humoral Immunitymentioning
confidence: 99%
“…In clinical practice, hyperacute rejection is very rare, and some initial reports suggested that liver allografts were much more resistant to humoral rejection than other solid organ allografts. [1][2][3] It is natural for the liver to be considered an 'immunologically privileged organ', and cadaveric donor liver transplantation is usually performed without considering human leukocyte antigen (HLA) matching. 4 However, other studies including the most recent reported that some cases of positive lymphocyte crossmatch or positive panel reactive antibody were associated with decreased liver graft survival.…”
mentioning
confidence: 99%
“…Difficulties are encountered in establishing the diagnosis because: 1 Liver allografts are large, able to absorb high antibody loads, especially anti-class I HLA [94], and are resistant to AMR-related damage [3,83,87,95,96]; 2 Immune deposits pointing toward an underlying injury cause are: (a) ephemeral [82,87]; (b) can be associated with other insults (see below); and (c) are more easily detected in frozen sections [97]; and 3 Clinicopathologic similarities exist between AMR and preservation injury, sepsis, and biliary or vascular complications [82,87]. Intrahepatic immune deposits are ephemeral in AMR, even when using the more sensitive technique of immunofluorescence on frozen tissue [30,82,87].…”
Section: Histopathologic Findingsmentioning
confidence: 99%